2006
DOI: 10.1309/hbmw-658q-fe44-x1vh
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Crystals Causing Falsely Elevated Automated Cell Count

Abstract: This is a report of 3 cases of body fluid containing numerous cholesterol crystals that caused falsely elevated cell counts on an automated cell counter. Two of the cases were pleural effusion fluid from patients with long-standing rheumatoid arthritis. Fluid in the third case was from upper extremity cystic lesions of a patient with squamous cell carcinoma of the head and neck. Microscopic examination revealed abundant cholesterol crystals in all fluid samples. In all 3 cases, initially, the automated cell co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…2,10 The WDF-PC/WDF-TC ratio is of particular relevance as it can point out an abnormal background due to interferences including yeast. [3][4][5][6][7][8][9]12 It was shown that many Candida species had a significant effect on the WBC count starting at 1-5 × 10 10 CFU/L (Sysmex XE-2100, Coulter LH 750, and ADVIA 120/2120) except for C. parapsilosis and C. glabrata that needed higher titers on the Sysmex XE-2100. The presence of EO > 5% was observed in the hemorrhagic CSF with C. albicans and with C. krusei in the first experiment, both from 8.8 × 10 8 CFU/L.…”
mentioning
confidence: 99%
“…2,10 The WDF-PC/WDF-TC ratio is of particular relevance as it can point out an abnormal background due to interferences including yeast. [3][4][5][6][7][8][9]12 It was shown that many Candida species had a significant effect on the WBC count starting at 1-5 × 10 10 CFU/L (Sysmex XE-2100, Coulter LH 750, and ADVIA 120/2120) except for C. parapsilosis and C. glabrata that needed higher titers on the Sysmex XE-2100. The presence of EO > 5% was observed in the hemorrhagic CSF with C. albicans and with C. krusei in the first experiment, both from 8.8 × 10 8 CFU/L.…”
mentioning
confidence: 99%
“…5 There is no evidence that raised serum cholesterol causes pseudochylothorax. 13 When it was measured, the serum cholesterol concentration was actually lower than the pleural fluid cholesterol concentration in two of our patients (patient C: serum cholesterol concentration, 240 mg/dL [6.2 mmol/L]; patient F: serum cholesterol concentration, 232 mg/dL [6.0 mmol/L]). The authors of a small study 16 hypothesized that low-density lipoprotein-bound cholesterol accumulates in the pleural space in acute inflammatory effusions.…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, if surgeons find yellow and turbid joint fluid during the operation, they usually make a diagnosis of septic arthritis and perform debridement or resection arthroplasty instead of THA. Lipid or cholesterol crystals in body fluids can cause a spurious elevation of WBCs in the automated cell count [10,25]. This artifact can occur in the automated WBC count of hip fluid containing marrow fat from an osteonecrotic femoral head and an erroneous diagnosis of septic arthritis can be made.…”
Section: Discussionmentioning
confidence: 99%
“…In certain situations, abnormal characteristics of the sample interfere and erroneous counts are obtained [25]. The most common causes are the presence of nucleated erythrocytes and failure of all the erythrocytes to lyse.…”
Section: Discussionmentioning
confidence: 99%